INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE FOR SPECIAL PURPOSES - Sergey S. Chromov; Nadezda A. Gulayeva; Irina S. Zelenetskaya (Статистика и экономика, 2016)
The paper is untended to draw attention to information communication technologiesin teaching Russian as a foreign language for special purposes at level B 2. In thisregard the educational process of teaching Russian as a foreign language is examinedfor promoting quality improvement in the process of ELT.Technology-enhances language learning(TELL) is described through computer-assisted language learning(CALL)-presentations, webinars, videolectures. The authors share their experience obtained during teaching Russian as a foreign language forspecial purposes at the Department of Linguistics and cross-cultural communicationat MESI University.